The Development of “Fact-Checking” Skills among Youth: The Main Condition for Establishing a Legal Democratic State Based on Spiritual and Moral Values - Khojaeva Malikakhon Nosirjon qizi (International Journal on Integrated Education, 2022)
Today, globalization and information processes are developing more and more intensively, “mass culture” and moral corruption are spreading worldwide, as well as attempts to achieve goals by harming the spiritual and moral values and education of young people in the fight against ideological processes, the social danger is increasing and becoming more and more clear. Therefore, the formation of information analysis skills among students is one of the most important issues, and in this article, the formation of “fact-checking” skills among students is taken as the main condition for the establishment of a legal democratic state based on moral and ethical values.